Assessment of electrocatalytic activity through the lens of three surface area normalization techniques. Issue 6 (22nd January 2020) - Ren, Hangjuan; Pan, Ying; Sorrell, Charles C.; Du, Haiwei
Abstract : Electrocatalytic activities of electrodes for water splitting are assessed via geometric area, BET surface area and ECSA normalisations. Abstract : Electrocatalytic activities of electrodes for water splitting generally are assessed in terms of current density normalisation on the basis of geometric area. However, this approach does not involve the effects of surface microstructure which often is rough. The present work examines this disagreement through the electrochemical characterisation of thermally treated carbon fibre paper in which the current density is normalised comparatively by geometric area, BET specific surface area and electrochemical active surface area (ECSA). The results show that the geometric area provides a nominal means of assessing the electrocatalytic activity. Since BET is effective in assessing the physical surface area, it provides a superior indication. However, ECSA provides the most discriminating means of assessment and reflects the intrinsic electrochemical activity.